2018
DOI: 10.1111/gcbb.12519
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of bacterial ammonium oxidizers and fungal denitrifiers in the complex nitrogen cycle pathways related to nitrous oxide emission

Abstract: Organic compounds and mineral nitrogen (N) usually increase nitrous oxide (N 2 O) emissions. Vinasse, a by-product of bio-ethanol production that is rich in carbon, nitrogen, and potassium, is recycled in sugarcane fields as a bio-fertilizer. Vinasse can contribute significantly to N 2 O emissions when applied with N in sugarcane plantations, a common practice. However, the biological processes involved in N 2 O emissions under this management practice are unknown. This study investigated the roles of nitrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 61 publications
2
25
0
3
Order By: Relevance
“…N content in the straw, 4.9 g kg −1 [6]. Tier 1 -IPCC approach; Tier 2 -Regional-specific approach based on data from this study Implications of Straw Removal for Soil N 2 O Emissions Despite being highly variable, the daily N 2 O emissions (ranging from 0.2 to 4.1 kg N 2 O-N ha −1 year −1 ) observed in this study are of the same magnitude as those reported in other studies conducted in sugarcane in Brazil [11,12,17,18,31]. The N 2 O emissions induced by N fertilizer plus straw removal in sugarcane fields were clearly site-specific (Fig.…”
Section: Implications Of Straw Removal For Soil Ch 4 Emissionssupporting
confidence: 73%
See 1 more Smart Citation
“…N content in the straw, 4.9 g kg −1 [6]. Tier 1 -IPCC approach; Tier 2 -Regional-specific approach based on data from this study Implications of Straw Removal for Soil N 2 O Emissions Despite being highly variable, the daily N 2 O emissions (ranging from 0.2 to 4.1 kg N 2 O-N ha −1 year −1 ) observed in this study are of the same magnitude as those reported in other studies conducted in sugarcane in Brazil [11,12,17,18,31]. The N 2 O emissions induced by N fertilizer plus straw removal in sugarcane fields were clearly site-specific (Fig.…”
Section: Implications Of Straw Removal For Soil Ch 4 Emissionssupporting
confidence: 73%
“…But once N is applied to the soil, several processes occur before N absorption by sugarcane plants, including volatilization, lixiviation, and/or N 2 O emission [16]. The latter is formed in the soil mostly by the microbial processes of nitrification and denitrification [17,18], which are highly influenced by moisture, temperature, and soil physical and chemical conditions. Methane (CH 4 ) is another important GHG (GWP of 28 times higher than CO 2 ) in agricultural environments [10], but so far little or no effect of straw maintenance on CH 4 emissions has been observed in Brazilian sugarcane fields [11,19], despite the higher soil moisture and organic C input caused by the straw mulching.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the increased nirS gene abundance, with no change in nirK gene abundance for soils with plants (Figure 4), we postulate that nirS genes are more sensitive to warming and probably contribute more to N 2 O production than nirK genes. However, fungal nirK genes that were not included in this meta‐analysis, might also play an important role in N 2 O production in terrestrial ecosystems (Laughlin & Stevens, 2002; Lourenço et al., 2018). This premise is based on the purported higher tolerance of fungal nirK genes to elevated temperatures (up to 40°C) compared to bacterial nirK genes (Xu et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the nitrite oxidizer bacteria Nitrobacter and Nitrospira have optimal growth under higher and lower nitrite supplies, respectively, which is linked to their ecological niches (Attard et al, 2010;Nowka et al, 2015). Nitrification is doubly implicated in N 2 O production, either directly or indirectly by producing NO 3 − as the basis for denitrification, and has been shown to be the main process involved in N 2 O emissions in some Brazilian sugarcane soils (Liu et al, 2016;Soares et al, 2016;Wu et al, 2017aWu et al, , 2017bLourenço et al, 2018aLourenço et al, , 2018b. The addition of nitrification inhibitors with nitrogen fertilizers is currently being explored as a sustainable management practice in Brazilian sugarcane Soares et al, 2015Soares et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%